Tax Revenue and Economic Growth in Nigeria: A Bi-Directional Approach (International Journal of Scientific Research and Management (IJSRM), 2024)
The study examined the bi-directional effect of tax revenue and economic growth in Nigeria from 2011 to 2022 by employing total tax revenue and nominal Gross Domestic Product at current price. Data was extracted from 2011 to 2022 quarterly reports published on the website of the Central Bank of Nigeria, National Bureau of Statistics and Federal Inland Revenue Service. Unit Root test using Augmented Dickey-Fuller (ADF) test shows that at the first difference, the variables are stationary at 1%, 5%, and 10% level of significance while Engle and Granger co-integration test reveals significant evidence of a long-run relationship between the variables of the study’s models. Findings from Error Correction Model (ECM) estimation show that Total Tax Revenue has a positive and significant effect on Nominal Gross Domestic Product (t-stat 4.777; P-value 0.000) and Nominal Gross Domestic Product has a positive and significant effect on Total Tax Revenue (t-stat 5.552; P-value 0.000). The Granger Causality test revealed that there exists a positive and significant bi-directional effect between Total Tax Revenue and Nominal Gross Domestic Product in Nigeria. The study concludes that tax revenue has a positive and significant effect on economic growth and economic growth has a positive and significant effect on tax revenue. The study recommends that the government ensure continuous economic growth by providing human capital, security, employment, and foreign investment. This would increase the standard of living of citizens, increase tax payer’s income, and attract foreign investors who would pay tax on their income and properties.